Significance of serum IP‐10/CXCL10 measurement in predicting post‐direct acting antiviral treatment liver function in patients with HCV‐decompensated liver cirrhosis. Issue 4 (13th December 2022) - Katoh, Ryo; Maekawa, Shinya; Osawa, Leona; Komiyama, Yasuyuki; Nakakuki, Natsuko; Takada, Hitomi; Matsuda, Shuya; Muraoka, Masaru; Suzuki, Yuichiro; Sato, Mitsuaki; Tatsumi, Akihisa; Takano, Shinichi; et al.
Abstract: Background: Recently, with the advent of sofosbuvir/velpatasvir therapy, sustained virological response (SVR) can now be achieved even in patients with decompensated cirrhosis (dLC). However, the prognosis after SVR does not always improve in dLC, and appropriate indicators enabling prediction of prognosis is desired. Patients and methods: Serum IP‐10/CXCL10 levels were measured in 47 patients (15 chronic hepatitis [CH], 17 compensated cirrhosis [cLC], and 15 dLC) receiving direct acting antiviral (DAA) therapy, and their changes during the therapy were examined. Results: All the patients achieved SVR. In patients with CH, the average IP‐10 level was 367, 102, and 68 pg/ml respectively at baseline, at the end of therapy and at 12 weeks after SVR (SVR12), and was decreased upon DAA therapy ( P  < 0.001). In patients with cLC, IP‐10 was respectively 215, 91, and 77 pg/ml, and was decreased upon DAA therapy ( P  < 0.001) while it was 283, 131, and 182 pg/ml in patients with dLC and there was no evident decrease ( P  = 0.55). When patients with dLC were further classified depending on the difference in Child–Pugh (CP) score improvement at SVR12, a significant decrease in IP‐10 was observed after treatment in those with improvement ( P  = 0.023) while a significant increase was observed in those without improvement ( P  = 0.016). Conclusion: While serum IP‐10 level was decreased in patients with CH/cLC and dLC with post‐SVR‐CP improvement following SVR, it was increased in patients with dLC without post‐SVR CP improvement. The result indicates that IP‐10 dynamics may be useful for predicting liver function after DAA therapy.